The integration of social criteria in sustainable design for furniture - Vicente, José (2011)
Sustainable design is a complex area that integrates a wide range of environmental, social and economic criteria. This paper is part of a research (www.designsustentavel.org) that intends to develop a toolkit and information for wood furniture designers to use in their work process and that should push this product range closer to the sustainable production and consumption system. In the course of this research it has been understood that the available information on social criteria is more general and difficult to implement by designers. Not only it appeared to be distant from the designer’s area of influence, but also too scarce and general when compared with environmental criteria already in use on ecodesign tools. The profusion of environmental criteria versus the lack of proper social criteria creates an imbalance on the available decision supporting criteria for the product development team. To tackle this problem the research team analysed the social issues proposed by ISO 26000 and conducted an expert workshop to establish relevant social criteria for this industrial sector that were within reach of the designer action. This paper presents (1) the process of selection, analysis, reflection and discussion of relevant subjects, (2) the effort to involve the stakeholders and (3) the main findings of this process considering the specific characteristics of the wood furniture sector in Portugal.